Implementation of the CIRC Method Assisted by Image Media to Improve Instructional Text Reading Skills for Slow Learners at Elementary School Level - Rabiatul Adawiyah; Mumpuniarti Mumpuniarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the process and effectiveness of instructional text reading skills in Indonesian Language Lessons through the CIRC method assisted by picture media in slow learner children at the elementary school level. The background of this study is the low reading comprehension ability of slow learner students caused by the lack of appropriate learning methods and media that are suitable for slow learner students. The method used in this study was the Classroom Action Research (CAR) model of Kemmis and Mctaggart, implemented in two cycles. The subjects were six slow-learning fifth-grade students of SD Negeri 002 Karangan. Data were collected through observation, learning test results, and documentation. The results of the learning test for reading instructional text skills showed a significant increase from cycle I to cycle II. In cycle I, 2 out of 6 slow learner students achieved the Minimum Completion Criteria (KKM), with an average score of 60 (classical completion 33.33%). While in cycle II, the number of students who completed the test increased to 5 out of 6 slow learner students with an average score of 80 (classical completion 83.33%). Based on these results, it can be concluded that the application of the CIRC method assisted by image media can successfully improve instructional text reading skills because it meets the score above the KKM and the students' active involvement in the learning process.